Filleted RDRA using novel ceramic dielectric (3G-BST) with stable gain and improved bandwidth for X-band application - Tripathi P.; Kumari P.; Sahu B.; Singh R.; Singh S.P.; Kumar D. (My University, 2025)
In the present communication, a filleted rectangular dielectric resonator antenna (FRDRA) using novel synthesized ceramic dielectric is described. The proposed antenna has dual segment rectangular structure filleted at the edges of its upper surface. Teflon (εr = 2.1) occupies lower segment of the structure and liquid phase (3 wt% of PbO-BaO-B2O3-SiO2 glass) sintered Ba0.5Sr0.5TiO3 (BST) namely 3G-BST (Average value of εr = 15) with filleted structure is used as upper segment. Liquid phase sintering reduces the manufacturing cost by reducing the sintering temperature of BST from 1250 °C to 950 °C without affecting the structure of ceramic with increasing density. The simulated impedance bandwidth of FRDRA is found to be 4.875 GHz (7.735–12.610 GHz), which is 8.57% greater than conventional dual segment rectangular dielectric resonator antenna (DS-RDRA). The experimental impedance bandwidth of FRDRA is 6.048 GHz (7.0–13.048 GHz). Among different feeding mechanisms, aperture-coupled feed mechanism is opted in the proposed antenna to reduce the spurious response and improve the antenna performance. Proposed FRDRA reduces material requirement and provides wider bandwidth with stable radiation pattern over its entire frequency band. The developed antenna is appropriate for use as primary feed in radar and satellite communication. © 2017 Elsevier Ltd and Techna Group S.r.l.